Analisis Kedudukan Notaris Sebagai Saksi dalam Proses Penyidikan Ditinjau dari Etika Profesi Notaris - Suriana, Ricky Kurniawan; Tay, Sherly; Saputro, Adi; Hutahean, Fendi Maruba Parlindungan (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
This study aims to analyze the legal position of notaries as witnesses in the investigation process based on the applicable laws and regulations. This research uses a normative legal research method. Data collection is carried out through library research, by examining legal documents and literature from libraries, online legal databases, and reliable academic sources. The obtained data is analyzed using qualitative analysis, which includes data reduction, data classification, legal interpretation, and drawing conclusions. The analysis results indicate that a notary's position as a witness in an investigation process is legally recognized, but its implementation must go through the approval mechanism of the Notary Honorary Council to maintain a balance between the interests of law enforcement and the protection of the confidentiality of the office. From the perspective of professional ethics, notaries face a dilemma between the obligation to maintain confidentiality and the duty to provide truthful testimony. The Notary Code of Ethics provides clear guidelines but still requires consideration of proportionality in its application. Harmonization between legal obligations and professional ethics can be achieved through the application of the principle of proportionality, optimization of the role of the Notary Honorary Council, limitation of the scope of testimony, and provision of adequate legal protection for notaries.